Meal skipping children in low-income families and community practice implications - Bae, Hwa-ok (The Korean Nutrition Society and The Korean Society of Community Nutrition, 2008)
We examined dietary habits, food intakes, health status, and school and community life of meal skipping children, and investigated factors predicting meal skipping of children. A sample was composed of 944 children in low-income families who were provided with public meal service. The sample was obtained from the Survey of Meal Service for Poor Children conducted by the Korea Institute for Health and Social Affairs in 2007. Meal skipping was significantly associated with a lower nutrition and health status, and poor school performance of children, as hypothesized. The school age of child, family structure, region, job of caretaker, concern about diet, and the child's visit to welfare center significantly predicted frequency of meal skipping. We suggested a few implications for community practice to reduce meal skipping of children.